2000
DOI: 10.1074/jbc.m908941199
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Phospholipase A2 Is Required for Macrophage Arachidonic Acid Release by Agonists That Do and Do Not Mobilize Calcium

Abstract: The 85-kDa cytosolic phospholipase A 2 (cPLA 2 ) mediates agonist-induced arachidonic acid release and eicosanoid production. Calcium and phosphorylation on Ser-505 by mitogen-activated protein kinases (MAPKs) regulate cPLA 2 . Arachidonic acid release and eicosanoid production induced by stimuli that do (A23187, zymosan) or do not (phorbol myristate acetate (PMA), okadaic acid) mobilize calcium were quantitatively suppressed in cPLA 2 -deficient mouse peritoneal macrophages. The contribution of MAPKs to cPLA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
183
4
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(213 citation statements)
references
References 65 publications
18
183
4
2
Order By: Relevance
“…The catalytic domain can affect membrane association of the enzyme by modulating the rate of association and also the residence time at membranes [18]. Furthermore, there is now convincing evidence that calcium-independent pathways for cytosol-to-membrane translocation of cPLA 2 -α exists [19][20][21][22][23][24], thus, suggesting alternative mechanisms for membrane association. One such mechanism could involve calcium-independent association of cPLA 2 -α to anionic phospholipids [21,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic domain can affect membrane association of the enzyme by modulating the rate of association and also the residence time at membranes [18]. Furthermore, there is now convincing evidence that calcium-independent pathways for cytosol-to-membrane translocation of cPLA 2 -α exists [19][20][21][22][23][24], thus, suggesting alternative mechanisms for membrane association. One such mechanism could involve calcium-independent association of cPLA 2 -α to anionic phospholipids [21,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of radiolabel studies, RPMs were reported to mobilize up to 50% of their 20:4 in response to the phagocytosis of zymosan, a yeast cell wall preparation that activates multiple receptors, including dectin-1 and toll-like receptor-2 (7). More than 90% of the radioactivity that appeared in the culture medium of zymosan-stimulated cells had been converted to eicosanoids, with the major metabolites identified as PGE 2 and PGI 2 (identified as its stable hydrolysis product, 6-ketoPGF 1R ), and minor quantities of hydroxyeicosatetraenoic acids. Leukotriene C 4 was identified later (5,(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…The primary means by which AA is released from membranes is the agonist induced activation of the calcium dependent group IV  isoform of cPLA 2 , due to its high specificity and selectivity for glycerophospholipids containing AA at the sn-2 position. Although the agonist induced activation of cPLA 2  has been established as the rate limiting step of eicosanoid biosynthesis (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), the deacylation of diacylglycerol (DAG) via DAG lipase also produces AA for the synthesis of eicosianoids. In addition, DAG lipase has been suggested to mediate the release of AA in KCs (56,62).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of cPLA 2 in eicosanoid production is further evident as cells and tissues from cPLA 2 -deficient mice fail to produce prostaglandins, leukotrienes, and thromboxanes (20,21). It is established that the primary function of cPLA 2  is to mediate agonist-induced release of AA for eicosanoid production (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The regulation of cPLA 2 activity involves multiple components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation